2023
DOI: 10.7759/cureus.34201
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal Carcinomatosis: A Rare Complication of Metastatic Gastric Cancer

Abstract: Leptomeningeal disease, also known as leptomeningeal carcinomatosis, occurs when cancer metastasizes to the meninges. This rare complication is associated with a poor prognosis. It is most commonly seen in patients with metastatic breast cancer, lung cancer, and melanoma. However, it is extremely rare in patients with metastatic gastric cancer.A 64-year-old female with poorly differentiated gastric adenocarcinoma metastatic to the peritoneum developed new neurological symptoms twelve months after initiating pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
0
4
1
Order By: Relevance
“…Brain metastasis is rare complication from esophageal and gastric cancer and our study showed an incidence over than 3%, while the average incidence in the literature ranges from 0.7% -6.6% (3,4,5,6,7,23). Leptomeningeal disease is even more rare with only few cases in the literature and the prevalence is estimated to be between 0.16% and 0.19% of gastric cancers [10], slightly lower than our study, 0.61%.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Brain metastasis is rare complication from esophageal and gastric cancer and our study showed an incidence over than 3%, while the average incidence in the literature ranges from 0.7% -6.6% (3,4,5,6,7,23). Leptomeningeal disease is even more rare with only few cases in the literature and the prevalence is estimated to be between 0.16% and 0.19% of gastric cancers [10], slightly lower than our study, 0.61%.…”
Section: Discussioncontrasting
confidence: 65%
“…Brain metastasis (BrM) and leptomeningeal carcinomatosis (LMC) are rare complications associated with gastroesophageal carcinoma (GEC). The occurrence of BrM ranges from 0.7% to 6.6% [3][4][5][6][7][8][9], while the incidence of LMC varies between 0.16% and 0.19% [10]. The complications are associated with neurologic morbidity and poor prognosis and quality of life [11], with median survival historically reported to be in the range of 2 to 6 months after its diagnosis [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 1%-8% of cancer patients in the United States are diagnosed with LMC [ 8 ]. LMC is a rare occurrence with gastric cancers but has been reported to be associated with 0.16%-0.19% of gastric cancers [ 10 ]. The most common subtype of gastric cancer associated with LMC is poorly differentiated adenocarcinoma with signet ring cell features [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…LMC occurs in 5-8% of patients with systematic malignancy [7,8]. Breast cancer has been considered the leading cause of LMC accounting for 11-64% of the overall incidence of LMC in solid tumors, followed by lung cancer (14-29%) and melanoma (6-18%) [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%